DINAMIKA PARAMETER OSEANOGRAFI TERHADAP HASIL TANGKAPAN IKAN TERI PADA BAGAN PERAHU DI TELUK DODINGA, KABUPATEN HALMAHERA BARAT - Jhon Karuwal (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2019)
Teri (Stolephorus spp) is the mainly catched of boat life nets in Bodinga Bay, West Halmahera district. The life of teri like other small pelagic fish was needed seas parameter as well as Its live needed. The aims of this study are to know the dynamic of sea’s parameter affected to boat liftnets catched in Dodinga Bay. The data of water’s parameters like sea surface temperature, salinity, water brightness, current velocity, wind speed and teri’s catches are collected by in situ way. Data analysis by using descriptic and statistic method to explain the connection between the factors with multiple linear regression method. The result of f test showing that all water’s parameters is together had have real impact on fish catches with fcount is 9.058 and significant values is less than 0.004 while the t test show that in individual parameter only wind speeds are had have real impact on teri catches with t test value is-3.010 at significant value is 0.005 (α= ( 0.05 ). The regression equation formed to explain the wind speed and anchovies catch him are = 526.666 - 72.513 X1 + e. Furthermore get also that the optimal of teri (Stolephorus spp) catches at Dodinga Bay was occurs on range of sea surface temperature are 24 – 28oC, salinitas of 25 - 30 ppt, wind speed of 0 - 2,5 m/s, current velocity are 0,1 - 0,7 m/s and the brightness of waters are 8-11 meters.